2000
DOI: 10.1038/sj.leu.2401644
|View full text |Cite
|
Sign up to set email alerts
|

Frequent deletions at 11q23 and 13q14 in B cell prolymphocytic leukemia (B-PLL)

Abstract: Deletions of the long arm of chromosomes 11 and 13 are the most frequent structural chromosome aberrations in various types of lymphoproliferative disorders. However, these regions have not been studied so far in B cell prolymphocytic leukemia (B-PLL). We have investigated the incidence of 13q deletions in 18 B-PLL cases by fluorescence in situ hybridization (FISH), using molecular probes for the RB1 and D13S25 loci. Chromosome 11q deletions were evaluated by FISH using the yeast artificial chromosome (YAC) cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(13 citation statements)
references
References 21 publications
0
12
0
1
Order By: Relevance
“…It is interesting to note that 11q23 deletion is also frequent in B cell prolymphocytic leukemia, which ususally has a fast progression. 36 A recent cDNA mRNA profiling analysis from this same patient cohort revealed some interesting gene expression patterns concerning CD14, CD25, CD79b. 37 CD25 mRNA was upregulated in 11q deletion patients.…”
Section: Discussionmentioning
confidence: 80%
“…It is interesting to note that 11q23 deletion is also frequent in B cell prolymphocytic leukemia, which ususally has a fast progression. 36 A recent cDNA mRNA profiling analysis from this same patient cohort revealed some interesting gene expression patterns concerning CD14, CD25, CD79b. 37 CD25 mRNA was upregulated in 11q deletion patients.…”
Section: Discussionmentioning
confidence: 80%
“…Studies of the 13q14 deletions in lymphoid neoplasia have indicated that RB1 may not be the affected gene in B cell NHL, 7,9 however, this situation may be different in other haematological neoplasms. 46,47 If the RB1 gene was the main target in the cases with 13q14…”
Section: Discussionmentioning
confidence: 99%
“…Only a few cytogenetic studies have been reported in B-PLL because of the rarity of the disease and the difficulty of obtaining prolymphocytes in metaphase. [50][51][52][53] Use of B-cell mitogens might increase the detection rate of cytogenetic changes. Complex karyotypic changes are common.…”
Section: How I Diagnose B-pllmentioning
confidence: 99%
“…Using interphase FISH, 13q14 deletions, 17p deletions, and monoallelic 11q23 deletions can be identified, but trisomy 12 is rare. 51 Other abnormalities described include 6qϪ, t(6;12), and structural aberrations of 1p and 1q. 50 Although t(11;14) has previously been described in B-PLL, it is clear now that these cases represent a leukemic phase of MCL, for which this is the "hallmark" translocation.…”
Section: How I Diagnose B-pllmentioning
confidence: 99%